2010
DOI: 10.1007/s00415-010-5632-2
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s disease: changes in saccades and hand-tapping over 3 years

Abstract: Saccades and hand-tapping are both potential biomarkers in patients with Huntington's disease (HD). While it is well known that patients with manifest Huntington's disease display abnormalities in both of these tasks, less is known about how these abnormalities progress over time, or to what extent premanifest patients are affected. This study was designed to address these issues. We examined premanifest and manifest Huntington's cohorts, together with a group of controls, over a 3-year period. Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…The usability of portable eye-tracking devices for severely impaired ALS patients, as has already been done in other neurological disorders [38] is another interesting aspect requiring further investigation. Additionally, more sophisticated eye-tracking controlled experimental procedures are warranted to investigate more subtle cognitive deficits in the physically impaired as well as individual distributions among patients.…”
Section: Discussionmentioning
confidence: 99%
“…The usability of portable eye-tracking devices for severely impaired ALS patients, as has already been done in other neurological disorders [38] is another interesting aspect requiring further investigation. Additionally, more sophisticated eye-tracking controlled experimental procedures are warranted to investigate more subtle cognitive deficits in the physically impaired as well as individual distributions among patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oculometry-using sophisticated measuring instruments rather than simple clinical examination-has been increasingly used as an experimental tool to gain insights into a wide range of neurological disorders. [2][3][4][5] Alzheimer's disease (AD)…”
mentioning
confidence: 99%
“…For example, quantitative measurements of eye movements such as saccade latency and duration, as well as errors in oculomotor tasks, have been studied as possible biomarkers of presymptomatic and early symptomatic stages of HD (Ali, Michell, Barker, & Carpenter, 2006;Blekher et al, 2006;Golding, Danchaivijitr, Hodgson, Tabrizi, & Kennard, 2006;Patel, Jankovic, Hood, Jeter, & Sereno, 2012). The results from clinical HD patients have consistently shown significantly increased saccadic latencies (Ali et al, 2006;Antoniades, Xu, Mason, Carpenter, & Barker, 2010;Avanzini, Girotti, Caraceni, & Spreafico, 1979;Blekher et al, 2006;Golding et al, 2006;Patel et al, 2012;Rupp et al, 2012), saccadic durations (Ali et al, 2006;Avanzini et al, 1979), and errors in saccadic direction (Blekher et al, 2006;Patel et al, 2012;Rupp et al, 2012). Also, increased saccadic latencies (Blekher et al, 2006;Golding et al, 2006;Robert et al, 2009) and errors in saccadic direction have been reported in presymptomatic stages (Blekher et al, 2006).…”
mentioning
confidence: 83%
“…When taking into account the known neuropathology in Huntington's disease and reported oculomotor deficits in manifest HD, our results seem to be in agreement with these factors. Both the DE and AE features reflect abnormalities of oculomotor performance in manifest HD, which parallels certain neurodegenerative processes-for example, marked deficits in voluntary saccade initiation and saccadic suppression, impersistent gaze, and increased incidence of anticipatory saccades (Ali et al, 2006;Antoniades et al, 2010;Blekher et al, 2006;Golding et al, 2006). HD's hallmark is well known to be striatal neural loss and atrophy (Aylward, 2007;Aylward et al, 2011), with altered functioning of the cortico-basal ganglia-thalamocortical circuitry (Joel, 2001); neurodegeneration spreads throughout the brain with disease progression .…”
Section: Discussionmentioning
confidence: 99%